Portable dual-axis solar tracking system with 3D printed structure and iot-based real-time energy monitoring - Mohd Nawari, Zarith Sofia; Roslan, Siti Sarah; Ibrahim, Izzah Afifah; Mohd Ghazali, Mohd Ifwat; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Solar radiation is one of the cleanest sources of renewable energy harvested throughout the world. However, the production of energy from the so-called "large-scale solar farm" is constrained by the availability of sunshine, with "peak sun hours" ranging from approximately four to six hours per day depending on the location of the solar panels. Solar panels installed on the ground or on roofs produce less power during sunrise and sunset than they do during the middle of the day. An automated solar tracking system, on the other hand, can increase energy production since it actively tracks the passage of the sun across the sky. When compared to their static counterparts, single-axis trackers can boost energy production by between 10 to 30%, while dual-axis trackers can enhance production by as much as 40%. This portable solar tracker, which was inspired by sunflowers, not only tracks the sun's movement in response to the presence or absence of light, but it also includes environmental sensors and an Internet-of-Things (IoT) energy monitoring system to provide real-time observation, data collection, and evaluate its overall performance. All these features are operated on this newly introduced simple portable energy monitoring device that comes together with customisable C programming language and python-based application to visualise all the data in real-time. This new development is adaptable for use in portable settings, such as in the military, in Search and Rescue (SAR) operations, and in leisure settings. Additionally, it has applications in the field of space exploration, particularly in satellites, planetary rovers, and the International Space Station (ISS).